Integrating the Old World into the New: an ‘Idol from the West Indies’ - Ostapkowicz, Joanna; Brock, Fiona; Widenhoeft, Alex C.; Schulting, Rick J.; Daviola, Donatella (Cambridge University Press, 2017)
The Pigorini cemí is an icon of Caribbean colonial history, reflecting early trans-Atlantic cross-cultural exchanges. Although well documented, the piece has received surprisingly little systematic study. We present the first structural analysis and radiocarbon dating of the sculpture (modelled at AD 1492–1524), and a brief discussion of the materials from which it is comprised. These include indigenous shell and European glass beads, newly identified feather and hair fibres, and the enigmatic rhinoceros-horn mask carved as a human face. We also address the sculpture's hidden internal wooden base, which is shown to be a non-indigenous display mount made of European willow (Salix sp.).